Algos gone wild: What drives the extreme order cancellation rates in modern markets? - Khomyn, Marta; Putniņš, Tālis J. (Journal of Banking & Finance, 2021)
97% of orders in US stock markets are cancelled before they trade, straining market infrastructure and raising concerns about predatory or manipulative trading. To understand the drivers of these extreme cancellation rates, we develop a simple model of liquidity provision and find that growth in order-to-trade ratios (OTTRs) is driven by fragmentation of trading and technological improvements that lower monitoring costs. High OTTRs occur legitimately in stocks with high volatility, fragmented trading, small tick sizes, and low volume. OTTRs are usually within levels consistent with market making, but occasionally spike to levels that may indicate illegitimate trading such as spoofing.